3D-Printing Graphene Scaffolds for Bone Tissue Engineering - Amber F. MacDonald; Meaghan E. Harley-Troxell; Steven D. Newby; Madhu S. Dhar (MDPI AG, 2022)
Graphene-based materials have recently gained attention for regenerating various tissue defects including bone, nerve, cartilage, and muscle. Even though the potential of graphene-based biomaterials has been realized in tissue engineering, there are significantly many more studies reporting in vitro and in vivo data in bone tissue engineering. Graphene constructs have mainly been studied as two-dimensional (2D) substrates when biological organs are within a three-dimensional (3D) environment. Therefore, developing 3D graphene scaffolds is the next clinical standard, yet most have been fabricated as foams which limit control of consistent morphology and porosity. To overcome this issue, 3D-printing technology is revolutionizing tissue engineering, due to its speed, accuracy, reproducibility, and overall ability to personalize treatment whereby scaffolds are printed to the exact dimensions of a tissue defect. Even though various 3D-printing techniques are available, practical applications of 3D-printed graphene scaffolds are still limited. This can be attributed to variations associated with fabrication of graphene derivatives, leading to variations in cell response. This review summarizes selected works describing the different fabrication techniques for 3D scaffolds, the novelty of graphene materials, and the use of 3D-printed scaffolds of graphene-based nanoparticles for bone tissue engineering.